OPTIMALISASI PEMASARAN DALAM MENGEMBANGKAN LEMBAGA PENDIDIKAN DI SEKOLAH DASAR ISLAM BAITUL MAKMUR MALANG - Suyono Suyono (STAI Ma'had Aly Al-Hikam Malang, 2020)
The existence of educational institutions depens on public interst, so that school are required to build a good image and good reputation of their educational institutations. Building a good image and good reputation of school on public requires a marketing. The marketing is not only how to intrpduce but also how tomake a feedback in the form of a sesnse of belonging the school, so the relationship between educatonal institutions and stakeholders are is well.The purpose of the research are: First, to describe the existing marketing in Sekolah Dasar Islam Baitul Makmur Malang. Second, to describe marketing optimalization for developing institutions in Sekolah Dasa Islam Batul Makmur malang.This study is qualitative research, case study type or field research. The method for collection the data are: observation, interviews and documentation. The analysis of data use; 1) data collection; 2) data condensation; 3) data presentation; 3) verification. The cheking of data use credibility and dependability.The results of this study are: 1) The marketing which used by Sekolah Dasar Islam Baitul Makmur Malang is implementation marketing mix, incuding product, price, place, promotion, physical evidence, people, and proses. 2) The optimalization of marketing is by make a special policy of every element marketing mix which pack those element marketing mix on promotion.